Association between the concurrence of pre-existing chronic liver disease and worse prognosis in patients with an herb- Polygonum multiflorum thunb. induced liver injury: a case-control study from a specialised liver disease center in China. Issue 1 (15th January 2019) - Jing, Jing; Wang, Rui-lin; Zhao, Xin-yan; Zhu, Yun; Niu, Ming; Wang, Li-fu; Song, Xue-ai; He, Ting-ting; Sun, Yong-qiang; Xu, Wen-tao; Yu, Si-miao; Wang, Li-ping; et al.
Abstract : Objectives: The present study aimed to evaluate the association between the concurrence of pre-existing chronic liver diseases (CLD) and worse prognosis in patients with HILI. Design: A case–control study. Setting: Tertiary hospital specialising in liver diseases in China. Participants: 145 hospitalised HILI patients were assessed with respect to prognosis by comparing HILI with or without pre-existing CLD from February 2007 to January 2017. Twenty-five HILI cases with pre-existing alcoholic liver disease (ALD) or non-alcoholic fatty liver disease (NAFLD) and 200 ALD or NAFLD controls matched 1:8 for sex, age (±4 years old), body mass index (±2 kg/m 2 ), the type of CLD, alcohol intake (±5 g/d) and the presence or absence of cirrhosis. Primary outcome measures: Mortality and chronicity in HILI patients with or without pre-existing CLD, and matched CLD patients. Results: Of the 193 714 hospitalised patients with liver diseases, 5703 patients met the diagnostic criteria for drug-induced liver injury (DILI), which was attributed to Polygonum multiflorum Thunb. (PMT) in 145 patients. Among these HILI patients, 22.8% (33 of 145) had pre-existing CLD, including 17 (51.5%) with ALD, 8 (24.2%) with NAFLD, 5 (15.2%) with chronic viral hepatitis and 3 (9.1%) with autoimmune liver disease. Compared with HILI patients without CLD, HILI patients with pre-existing CLD showed higher mortality (0.9% vs 9.1%, p=0.037) and higher chronicity (12.5% vs 30.3%, p=0.016). Compared with matched ALD (136 patients) or NAFLD (64 patients) patients, HILI patients with pre-existing ALD showed higher chronicity (35.3% vs 11.8%, p=0.019). Multivariate logistic regression analysis found that concurrence of pre-existing CLD was an independent risk factor for both of chronicity and mortality (OR 3.966, 95% CI 1.501 to 10.477, p=0.005), especially the chronicity (OR 3.035, 95% CI 1.115 to 8.259, p=0.030). Conclusions: Concurrence of pre-existing CLD could be an independent risk factor for worse prognosis, especially chronicity, in PMT-related HILI.